Integrating Advanced ICT Tools for Promoting Student Engagement and Academic Performance in Malian Higher Education - Drissa Kante; Youssouf Kayentao; Akpaasou Daniel Terver (The Indonesian Institute of Science and Technology Research, 2026)
This work shows that the use of ICT in Malian Higher Education has significantly improved both student engagement and academic performance, with increases in the average GPA, graduation rate, and digital literacy. E-learning platforms, mobile apps, AI, and virtual reality offer transformative potential, but infrastructure gaps, inadequate faculty training, and pedagogical resistance remain barriers. Successful ICT integration requires more than technology deployment; it demands strong leadership, sustained funding, flexible teaching practices, and contextually relevant, mobile-friendly approaches. Private colleges are outperforming public institutions, revealing systemic inequalities that need policy intervention. To bridge the digital divide, efforts should focus on improving infrastructure, expanding digital skills training for community leaders, and revamping curricula to include digital literacy. Ultimately, unlocking ICT’s full educational potential depends on multi-stakeholder collaboration among policymakers, educators, tech providers, and students to build inclusive, sustainable learning ecosystems. Such initiatives will prepare Malian graduates for participation in the global digital economy.